Indicadores de desempenho e o seu alinhamento ao planejamento estratégico. Um estudo de caso em uma indústria do setor moveleiro - Porto, Adriana (2005)
The present work has the aim of proposing a model of performance indicators that reflex the strategic perspective adopted by an industry of the furniture sector. It is understood that the use of indicators is linked to the strategic administration, because they enable the development of a view of the future and of the organizational strategy in measures of performance. According to Eclles (2000) and Kaplan & Norton (2000), the administrators have perceived that the new strategies and the new competitive reality require new systems of measurement which include a balanced set of indicators that allow them to visualize the company under several perspectives at the same time. This way, through the methodology of case study it is possible to collect information and structure a model of indicators which supported the strategy and helped to make the decision with the referred model, it was intended initially to identify and analyze the existent indicator models through the study of the available theorical referential, observing two main methodologies of measurement of the performance which are: the Balanced Scorecard proposed by Kaplan & Norton (1997) and the dashboard suggested by the Thematic Committee of Measurement of the Foundation Performance to the National Prize of Quality. Next, the aim was to describe the structure of the furniture sector in the world, national, and state field standing out the critical factors to the competitiveness of this industry. After the survey of the theorical reference base, it was collected information related to the future view and to the strategic planning of the company, standing out the inner and outer analysis and the strategic questions defined in the plan. The theory exchange with the company data allowed the development of the model of indicators structured in five perspectives: financial, market/clients, innovation, inner processes, learning and growth. The building of the model followed the principles of the relation cause and effect, definition of trend indicators (lead indicators) and result indicators (lag indicators). Initially a strategic map was built with the demonstration of the set of hypotheses that connects the strategic questions, defining the organizational perspectives. For each perspective, then, determine the critical factors of success and their interrelationship, that allowed the definition of the performance indicators more adequate to the strategic choices made by the company. Finally, it was built a map of the indicators that allows the visualization of the development of the strategic questions, permitting that the organizations see their strategies in a coherent, integrated and systematic way. The model of indicators allows a clear comprehension of the strategic options, contributing to a conquest of better management practices and professionalization of the company.